Kinetic mechanism and fidelity of nick sealing by Escherichia coli NAD(+)-dependent DNA ligase (LigA) - Chauleau, Mathieu (Nucleic Acids Res, 2016)
Escherichia coli DNA ligase (EcoLigA) repairs 3′-OH/5′-PO(4) nicks in duplex DNA via reaction of LigA with NAD(+) to form a covalent LigA-(lysyl-Nζ)–AMP intermediate (step 1); transfer of AMP to the nick 5′-PO(4) to form an AppDNA intermediate (step 2); and attack of the nick 3′-OH on AppDNA to form a 3′-5′ phosphodiester (step 3). A distinctive feature of EcoLigA is its stimulation by ammonium ion. Here we used rapid mix-quench methods to analyze the kinetic mechanism of single-turnover nick sealing by EcoLigA–AMP. For substrates with correctly base-paired 3′-OH/5′-PO(4) nicks, k(step2) was fast (6.8–27 s(−1)) and similar to k(step3) (8.3–42 s(−1)). Absent ammonium, k(step2) and k(step3) were 48-fold and 16-fold slower, respectively. EcoLigA was exquisitely sensitive to 3′-OH base mispairs and 3′ N:abasic lesions, which elicited 1000- to >20000-fold decrements in k(step2). The exception was the non-canonical 3′ A:oxoG configuration, which EcoLigA accepted as correctly paired for rapid sealing. These results underscore: (i) how EcoLigA requires proper positioning of the nick 3′ nucleoside for catalysis of 5′ adenylylation; and (ii) EcoLigA's potential to embed mutations during the repair of oxidative damage. EcoLigA was relatively tolerant of 5′-phosphate base mispairs and 5′ N:abasic lesions.